RESTRUCTURING OF AGRO-INDUSTRIAL ENTERPRISES AS A MEANS OF ADAPTING TO MODERN CHALLENGES - STAROV, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The relevance of the topic of restructuring agro-industrial enterprises is due to several modern challenges faced by agriculture and the agro-industrial sector in a global context. Economic instability and war, increased competition and globalization of markets, climate change, demand for environmentally friendly and innovative products, and technological development are the main reasons that enhance the importance of the research topic. Despite the significant number of scientific works on the topic under study, considering modern challenges and business conditions, these issues require further research.The article is devoted to the study of the processes of restructuring agro-industrial enterprises to adapt to modern challenges.It is proved that the restructuring of agro-industrial enterprises consists of complex changes in the structure, processes, and management of the enterprise, which allows it to effectively respond to new market challenges, technological innovations, climate change, and changes in demand. Its essence lies in the renewal and optimization of all elements of the activity of an agro-industrial enterprise to increase competitiveness, sustainability, and adaptability.It is substantiated that the restructuring of agricultural enterprises can take various forms, depending on the goals, specifics of the activity, and the state of the enterprise: financial, operational, organizational, legal, innovative, social, and environmental. Each of these forms can be used both separately and in combination.The principal modern mechanisms for restructuring agricultural enterprises in the system of integration relations are identified, which allow such enterprises to respond to the challenges of the modern market effectively, ensuring stable development and integration into international supply chains.
Keywords: agro-industrial enterprises; economic instability; innovation; integration relations; competition; restructuring